2018
DOI: 10.1080/21645515.2018.1455476
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of simultaneous versus sequential administration of a 23-valent pneumococcal polysaccharide vaccine and a quadrivalent influenza vaccine in older individuals: A randomized, open-label, non-inferiority trial

Abstract: It is unclear whether simultaneous administration of a 23-valent pneumococcal polysaccharide vaccine (PPSV23) and a quadrivalent influenza vaccine (QIV) produces immunogenicity in older individuals. This study tested the hypothesis that the pneumococcal antibody response elicited by simultaneous administration of PPSV23 and QIV in older individuals is not inferior to that elicited by sequential administration of PPSV23 and QIV. We performed a single-center, randomized, open-label, non-inferiority trial compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Simultaneous administration of IIV4 and 23-valent pneumococcal polysaccharide vaccine (PPSV23) to persons aged ≥65 years was associated with lower seroprotection rates to one influenza B antigen at 4-6 weeks postvaccination as compared with sequential administration 2 weeks apart; seroprotection was not significantly different between the two groups for any of the four influenza antigens at 6 months postvaccination (88). Reassuring safety profiles have been noted for simultaneous administration of IIVs with live attenuated zoster vaccine (83,84), PCV13 (85,86), PPSV23 (88,89), and tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis (Tdap) vaccine among adults (87) and of Tdap among pregnant women (90). Although increased prevalence of injection site or systemic adverse reactions has been noted with concurrent administration in some of these studies, these symptoms have generally been reported to be mild or moderate.…”
Section: Administration Of Influenza Vaccines With Other Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous administration of IIV4 and 23-valent pneumococcal polysaccharide vaccine (PPSV23) to persons aged ≥65 years was associated with lower seroprotection rates to one influenza B antigen at 4-6 weeks postvaccination as compared with sequential administration 2 weeks apart; seroprotection was not significantly different between the two groups for any of the four influenza antigens at 6 months postvaccination (88). Reassuring safety profiles have been noted for simultaneous administration of IIVs with live attenuated zoster vaccine (83,84), PCV13 (85,86), PPSV23 (88,89), and tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis (Tdap) vaccine among adults (87) and of Tdap among pregnant women (90). Although increased prevalence of injection site or systemic adverse reactions has been noted with concurrent administration in some of these studies, these symptoms have generally been reported to be mild or moderate.…”
Section: Administration Of Influenza Vaccines With Other Vaccinesmentioning
confidence: 99%
“…In some studies, reduced responses have been noted to 13-valent pneumococcal conjugate vaccine (PCV13) ( 85 , 86 ), tetanus antigens ( 87 ), and pertussis antigens ( 87 ) when co-administered with IIV3 to adults; in most instances, the clinical significance of this is uncertain. Simultaneous administration of IIV4 and 23-valent pneumococcal polysaccharide vaccine (PPSV23) to persons aged ≥65 years was associated with lower seroprotection rates to one influenza B antigen at 4–6 weeks postvaccination as compared with sequential administration 2 weeks apart; seroprotection was not significantly different between the two groups for any of the four influenza antigens at 6 months postvaccination ( 88 ). Reassuring safety profiles have been noted for simultaneous administration of IIVs with live attenuated zoster vaccine ( 83 , 84 ), PCV13 ( 85 , 86 ), PPSV23 ( 88 , 89 ), and tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis (Tdap) vaccine among adults ( 87 ) and of Tdap among pregnant women ( 90 ).…”
Section: Recommendations For the Use Of Influenza Vaccines 2020–21mentioning
confidence: 99%
“… 11 Moreover, the combination of a new quadrivalent influenza vaccine and 23-valent pneumococcal polysaccharide vaccine was suggested to have an acceptable immunogenicity that is comparable to sequential administration without an increase in adverse reactions for elderly Japanese people. 12 …”
Section: Evidence On Combined Use Of Both Vaccinesmentioning
confidence: 99%
“…9 Co-administration of different vaccines results to be immunogenic and well-tolerated as described in several papers. 15 - 17 To cite some examples, Nakashima et al 18 and Thompson et al 19 concluded that co-administration of the quadrivalent influenza vaccine and the 23-valent pneumococcal polysaccharide vaccine (PPV23) and with the 13-valent pneumococcal polysaccharide conjugate vaccine (PCV13) respectively, is a safe and effective practice and does not lead to an increase in adverse reactions. 18 , 19 Several authors evaluated the safety and immunogenicity of the quadrivalent meningococcal conjugate vaccine (Men ACWY) co-administered with common childhood vaccines, confirming good tolerability, elevated immunogenicity, and safety.…”
Section: Introductionmentioning
confidence: 99%
“… 15 - 17 To cite some examples, Nakashima et al 18 and Thompson et al 19 concluded that co-administration of the quadrivalent influenza vaccine and the 23-valent pneumococcal polysaccharide vaccine (PPV23) and with the 13-valent pneumococcal polysaccharide conjugate vaccine (PCV13) respectively, is a safe and effective practice and does not lead to an increase in adverse reactions. 18 , 19 Several authors evaluated the safety and immunogenicity of the quadrivalent meningococcal conjugate vaccine (Men ACWY) co-administered with common childhood vaccines, confirming good tolerability, elevated immunogenicity, and safety. 20 24 Finally, with regard to the concomitant administration of meningococcal C conjugated vaccines (as tetravalent or monovalent vaccines) and MMRV, which will be further investigated in the course of this review, in recent studies performed by Durando et al 5 and Klein et al, 2 this co-administration appears to be well tolerated, without safety issues and with a good immune response for both vaccines.…”
Section: Introductionmentioning
confidence: 99%